Elements For Effective Design Of Abrasion Resistant Concretes - D. van Heerden (The Southern African Institute of Mining and Metallurgy, 2005)
In the mining industry abrasion caused by both sliding and impact have over the years resulted in costly damage to installations such as ore passes and silos. Good geotechnical practices combined with the use of a high quality abrasion resistant concrete can prolong the life of such an installation and minimize problems associated with abrasion. In order to maximize the life of an abrasion resistant concrete, the choice and combination of the correct raw materials (cement, aggregate and fibre) and overall mix design needed to make up such a concrete are important. This paper presents technical data and practical experience showing that concrete formulated with calcium aluminate cement resists severe abrasion conditions better than similar OPC-based concretes.